ANALISIS LINK BUDGETING BERBASIS GUI (GRAPHICAL USER INTERFACE) MATLAB PADA DAERAH PUSAT KOTA (DPK), PERKANTORAN, DAN PERUMAHAN - ., Eko Saputra (Faculty of Engineering, Universitas Tanjungpura, 2018)
At this time, the need for wireless communication is so high that a wireless communication network planning is required. In the planning of wireless communication system required calculation of link budget which is the loss calculation from antenna transmitter to receiver. The calculation of link budgeting has an important role for communication network design to achieve optimum and efficient results both in terms of technical reliability and cost. Therefore in this final task has been made a visualization software link budget calculation from GSM providers in urban areas of the City Center (DPK), Office and Housing. The data used in the calculation of GSM link budget is the measurement data with the drive test method and data obtained from PT. Telkomsel as reference data from each BTS used as research material. From the data is calculated pathloss value and power level received. To calculate the path loss and receive power level in the urban area using the COST 231 Walfisch Ikegami model and the application used is matlab. Based on Path loss Link Budgeting software that has been created with high base stations that have the strongest signal quality is the City Center with a Power Level Accept of -51 dBm and the lowest -53 dBm, the smallest path loss 101.8 dB and the largest 103, 8 dB, whereas the weakest quality area is the residential area with the strongest receptivity level is -51 and the lowest is -63 with the smallest path loss 101,8 dB and biggest 113,8 dB. Keywords : Path Loss, link budget, COST 231 Walfisch Ikegami model